The electrical stimulation of the central nucleus of the amygdala in combination with dopamine receptor antagonist reduces the acquisition phase of morphine-induced conditioned place preference in male rat - Zahra Jokar; Saeed Khatamsaz; Hojjatallah Alaei; Mehrdad Shariati (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: The central nucleus of the amygdala (CeA) is one of the nuclei involved in the reward system. The aim of the current study was to investigate the electrical stimulation (e-stim) effect of the CeA in combination with dopamine D1 receptor antagonist on morphine-induced conditioned place preference (CPP) in male rats. Experimental approach: A 5-day procedure of CPP was used in this study. Morphine was administered at an effective dose of 5 mg/kg, and SCH23390 as a selective D1 receptor antagonist was administrated into the CeA. In addition, the CeA was stimulated with an intensity of the current of 150 μA. Finally, the dependence on morphine was evaluated in all experimental groups. Findings /Results : Morphine significantly increased CPP. While the blockade of the D1 receptor of the CeA reduced the acquisition phase of morphine-induced CPP. Moreover, the combination of D1 receptor antagonist and e-stim suppressed morphine-induced CPP, even it induced an aversion. Conclusion and implication : The current study suggests that the administration of dopamine D1 receptor antagonist into the CeA in combination with e-stim could play a prominent role in morphine dependence.